2017
DOI: 10.12816/0039689
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Tuberculosis among General Populations in Riyadh Region and Its Surroundings

Abstract: Background: In the past, and until the end of the twentieth century, TB was one of the major causes of death. Nowadays, the world is still challenging with TB control, even though the percentage of TB has been decreased. In Saudi Arabia, annual TB incidence rate is 12/100,000 population. Even though incidence rate of TB has been decreased in Saudi Arabia, still TB not fully control. Getting the world free from TB will not happen if general populations don't aware about TB. Aim: To evaluate knowledge, attitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Research conducted in Libya with a large sample also demonstrated limited knowledge, indicating the need for education on this subject [12]. However, most participants in our study had heard about TB (65.6%) and knew that bacteria cause it (48%), which is somewhat satisfactory in comparison to a study conducted in Riyadh revealing that only 35% of the participants knew the cause of TB [13]. The different study locations may explain this variation because TB is more prevalent in Makkah, affecting Saudis and non-Saudis equally.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Research conducted in Libya with a large sample also demonstrated limited knowledge, indicating the need for education on this subject [12]. However, most participants in our study had heard about TB (65.6%) and knew that bacteria cause it (48%), which is somewhat satisfactory in comparison to a study conducted in Riyadh revealing that only 35% of the participants knew the cause of TB [13]. The different study locations may explain this variation because TB is more prevalent in Makkah, affecting Saudis and non-Saudis equally.…”
Section: Discussioncontrasting
confidence: 75%
“…Similar reasons were mentioned in southwest Ethiopia and Vietnam [21,25]. However, a study in Riyadh revealed that 67.6% of the general population had good practice knowledge, which could be a result of their high level of education and good healthcare-seeking behavior [13].…”
Section: Discussionmentioning
confidence: 56%